PENGARUH MENGKONSUMSI GULA AREN (Arenga pinnata) SEBELUM OLAHRAGA TERHADAP DAYA TAHAN OTOT - Cecep Muhammad Alawi; Hamidie Ronald Daniel Ray (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2019)
Two kinds of carbohydrates that are used with the body as energy, is blood glucose and muscular glycogen. Savings glycogen in muscular is one of the factors that is affecting muscular endurance when physical exercise. The aim of this study is to find out the significant influence of consuming palm sugar to muscular endurance before physical exercise. The method that is used in this study is to experiment with design pretest-posttest control group design. Total of sample of this study is 18 trained mans that is divided into three groups. The first experiment group is given palm sugar that is dissolved in water, the second experiment group is given sugar that is dissolved in water, and the control group is given mineral water. The instrument of this study is used push up test, sit up test, and squat jump test to measures the upper muscular endurance, middle, and bottom. All of the samples have done pretest and posttest in different day. When posttest, all of the sample is consumed beverage based on the treatment 30 minutes before do the posttest. Data analysis by Paired Sample t-test and continued by One Way ANOVA to see the influence and comparison between groups. The result of this study has showed that there is a significant difference, the raising of muscular endurance is proved by the score (sig) 0.00>0.05, which the highest increasing is the palm sugar group. Therefore, it could be concluded that there is a significant influence of consuming palm sugar to muscular endurance before physical exercise.